(untitled) (Development Service Industry Management, 2024)
In the conditions of the modern global knowledge economy, innovative activity becomes a key factor in the competitiveness of enterprises. The main driver of this activity is intellectual property, which includes patents, copyrights, trademarks and other forms of legal protection of innovative ideas and developments. However, despite the obvious benefits, many businesses face challenges in effectively using intellectual property tools to drive innovation. The lack of proper understanding of the role of intellectual property, as well as the complexity and cost of its protection, often prevent the maximum use of the potential of innovative activity. Scientific research on the relationship between intellectual property and the knowledge economy is important for a deeper understanding of the mechanisms of innovation stimulation. This includes studying models that describe how intellectual property can influence the creation of new knowledge and technology. Practical studies of the impact of intellectual property protection and the economic results of enterprises will help to identify the most effective strategies for innovative activities. This includes assessing the economic benefits of patenting, licensing and other forms of intellectual property protection. Studying the role of intellectual property in stimulating the innovative activity of enterprises is of great importance both for the development of the theoretical foundations of the knowledge economy and for solving practical problems related to increasing the competitiveness and economic efficiency of enterprises. The article examines the role of intellectual property in the knowledge economy as a key tool for stimulating the innovation activities of enterprises. The knowledge economy plays a crucial role in the modern world, where intellectual resources become key drivers of economic growth and competitiveness. In this context, intellectual property is a critically important tool for stimulating the innovation activities of enterprises. This article explores the role of intellectual property in stimulating innovation by analyzing its impact on the economic performance of enterprises, innovation activity, and licensing opportunities. The research results indicate that enterprises actively using intellectual property demonstrate higher financial performance and greater activity. However, there are barriers such as high patenting costs and the complexity of law enforcement that reduce the motivation to protect innovations. The article also offers recommendations for overcoming these barriers and effectively managing intellectual property, which can contribute to the development of innovative activities of enterprises.